2020
DOI: 10.3389/fncel.2020.580206
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Mucosa Mesenchymal Stem Cells Ameliorate Cerebral Ischemic/Reperfusion Injury Through Modulation of UBIAD1 Expression

Abstract: Mesenchymal stem cells (MSCs) have presented a promising neuroprotective effect in cerebral ischemia/reperfusion (I/R). Olfactory mucosa MSCs (OM-MSCs), a novel source of MSCs located in the human nasal cavity, are easy to obtain and situated for autologous transplantation. The present study was designed to evaluate the neuroprotective effects of OM-MSCs on cerebral I/R injury and the possible mechanisms. In the transient middle cerebral artery occlusion (t-MCAO) model, excessive oxidative stress and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…Previously, we discovered that UBIAD1 exhibits multi-subcellular organelles colocalization in mouse N2A neuroblastoma cells, including in the mitochondria, endoplasmic reticulum, and Golgi apparatus 26 . Up-regulating the expression of UBIAD1 could attenuated cerebral ischemia/reperfusion-induced mitochondrial fragmentation and dysfunction 38 , and ameliorated the fragmentation and reduced the level of oxidative stress-related protein expression in both the endoplasmic reticulum and Golgi apparatus.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, we discovered that UBIAD1 exhibits multi-subcellular organelles colocalization in mouse N2A neuroblastoma cells, including in the mitochondria, endoplasmic reticulum, and Golgi apparatus 26 . Up-regulating the expression of UBIAD1 could attenuated cerebral ischemia/reperfusion-induced mitochondrial fragmentation and dysfunction 38 , and ameliorated the fragmentation and reduced the level of oxidative stress-related protein expression in both the endoplasmic reticulum and Golgi apparatus.…”
Section: Discussionmentioning
confidence: 95%
“…Although we suggested that hypoxic OM-MSCs inhibited microglial pyroptosis in ICH, the specific mechanism of the inflammatory response of microglia regulated by hypoxic OM-MSCs after ICH injury is still unclear. Previously, we demonstrated that OM-MSCs exerts neuroprotective effects on cerebral ischemia/reperfusion injury (47,48,50). We also revealed that hypoxia-preconditioned OM-MSCs inhibit pyroptotic death of microglial cells by activating the hypoxia inducible factor-1α (HIF-1α) in vitro model of ischemic stroke (49).…”
Section: Effects Of Mscs On Microglial Pyroptosis Post-ichmentioning
confidence: 97%
“…Olfactory mucosa MSCs (OM-MSCs) localized in the nasal lamina propria have recently been recognized as an ideal source of MSCs, as they are easily accessible and situated for autologous transplantation (46). Previously, we demonstrated that OM-MSCs exerts neuroprotective effects in ischemic stroke (47,48). We also revealed that hypoxia-preconditioned OM-MSCs inhibited microglial pyroptosis in an in vitro model (49) and affirmed that hypoxic preconditioning enhanced the therapeutic efficacy of OM-MSCs in an in vivo model (50).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2012a) have found that adipose-derived mesenchymal stem cells (ADMSCs) attenuated cerebral ischemia-reperfusion injury through suppressing iNOS. Another two interesting findings indicated that olfactory mucosa mesenchymal stem cells (OM-MSCs) exert neuroprotective effects by rescuing the function of mitochondria and Golgi apparatus and enhancing antioxidation via upregulation of UBIAD1 and SPCA1 (He et al, 2020;Liu et al, 2020b). Moreover, that MSCs modified with diverse molecules exhibited antioxidative stress effects on ischemic stroke models have also been reported, such as C-C motif chemokine receptor 2 (CCR-2), brain-derived neurotrophic factor (BDNF), and circRNA-Akap7 (Lu et al, 2016;Huang et al, 2018b;Xu et al, 2020).…”
Section: Mscs Inhibit the Production Of Ros And Rnsmentioning
confidence: 99%